Diseño y construcción de un prototipo de impresora 3d con ambiente cerrado para la impresión de materiales especiales - Olivo Molina, Roosevelt Rafael (2022)
In the present technological proposal, the design and construction of a 3D printer with a closed environment was carried out for the manufacture of parts with more resistant materials such as: ABS, Nylon, TPU, Carbon Fiber among others. These materials require a temperature higher than 240ºC for casting, also requires a closed environment to prevent air currents from affecting the printing process. The problem is the deficiency of a 3D printer with a closed environment in the CIYA laboratories, since the students require this tool for the construction of parts with technical materials, as a solution to the problem, a printer prototype was built so that the students can to make use in the elaboration of projects of robotics, mechanics and electronics. This project was carried out using several methodologies, one of the most important is the scientific one where a study of loads acting on the structure was carried out, the Inventor software was used for modeling and to determine the maximum effort. For the dimensioning of the capacity of the sources, Ohm's law was used to determine the power of each load and the total. In the construction, electronic and mechanical components existing in the country were selected, after assembly, tests were carried out with three materials such as ABS, Nylon and TPU. It was found that each material has a different printing temperature, not all materials require a closed environment, for ABS and Nylon it is necessary that the printer be closed, while TPU does not require any enclosure. When the pieces were printed with the different materials, the printing parameters were taken into account, they were established in the Cura software, and it has the function of generating the G code, for the printing process.